Persepsi Konsumen Terhadap Pembelian Pangan Lokal Kupu (Studi Kasus Pada Industri Rumah Tangga Griya Jawau Melin Kelurahan Bukit Tunggal Kecamatan Jekan Raya Kota Palangka Raya) - Dina Graselita Putri; Emmy Uthanya Antang; Tri Yuliana Eka Sinta (Jurnal Kaharati, 2021)
This study aims to: (1) to know the consumer's characteristics of local food kupu (made of cassava), and (2) to know consumer perceptions of local food kupu. This research was a case study at the Home Industry "Griya Jawau Melin". The number of samples was 35 respondents, which has been specified with a convenience sampling technique. The research was designed both qualitative and quantitative methods, Data were collected through interviews with a questionnaire guide, and data were analyzed descriptively and using a Likert Scale. These results indicate that kupu consumers have varied characteristics, including gender, age, ethnic, education, occupation, and income. Consumers' perceptions of local food kupu which consist of variables i.e. taste, quality, price, sosial, and culture, are considered good with a score of 3203 and an average score of 79.58. The variable that gives the highest score was a culture with an average score of 84.57, followed by sosial variables (average score 81.94), quality variable (average score 81.55), price variable (average score 77, 90), and lastly, the taste score with an average of 69.43. These results indicate that the most influencing purchases are cultural and sosial faktors, the taste faktor being the last variable influencing the purchase of Kupu after the quality and price variables.